A sinonasal yolk sac tumor in an adult - Jaehoon Shin; Ji Heui Kim; Kyeong Cheon Jung; Kyung-Ja Cho (Korean Society of Pathologists & the Korean Society for Cytopathology, 2022)
Yolk sac tumors (YSTs), which are also called endodermal sinus tumors, are malignant tumors of germ cell origin. These tumors usually occur in the gonads, but 20% of cases have been reported at extragonadal sites. The head and neck is a rarely affected region that accounts for just 1% of all malignant tumors of germ cell origin. In addition, YSTs arise mostly in childhood. We present a rare pathologically pure case of primary adult YST in the sinonasal area. A 45-year-old male patient presented with a rapidly growing mass in the nasal cavity, which caused nasal obstruction and bloody post-nasal drip. The histopathologic features indicated pure YST, and immunohistochemical analysis revealed positive reactivity for Sal-like protein 4 and alpha-fetoprotein. Herein, we discuss the clinical, radiologic, and histologic features of this YST and review other cases of sinonasal YST in adults.